2015
DOI: 10.1038/srep16554
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Toxin Resistance Enables Pink Bollworm Survival on Pyramided Bt Cotton

Abstract: Transgenic crops producing Bacillus thuringiensis (Bt) proteins kill key insect pests, providing economic and environmental benefits. However, the evolution of pest resistance threatens the continued success of such Bt crops. To delay or counter resistance, transgenic plant “pyramids” producing two or more Bt proteins that kill the same pest have been adopted extensively. Field populations of the pink bollworm (Pectinophora gossypiella) in the United States have remained susceptible to Bt toxins Cry1Ac and Cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 57 publications
0
48
0
Order By: Relevance
“…In the USA, PBW pestilence and resistance development have been effectively managed by pheromone‐based monitoring, implementation of integrated pest management (IPM) programs, including release of male sterile moths, planting of refuges and cultivation of stacked‐gene transgenic cotton . These strategies have ensured that the pest is still under control and resistance development has been delayed . In China, a small but statistically significant increase in PBW resistance to Cry1Ac was reported in the Yangtze River Valley from 2005 to 2010, but resistance did not increase until 2015 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the USA, PBW pestilence and resistance development have been effectively managed by pheromone‐based monitoring, implementation of integrated pest management (IPM) programs, including release of male sterile moths, planting of refuges and cultivation of stacked‐gene transgenic cotton . These strategies have ensured that the pest is still under control and resistance development has been delayed . In China, a small but statistically significant increase in PBW resistance to Cry1Ac was reported in the Yangtze River Valley from 2005 to 2010, but resistance did not increase until 2015 .…”
Section: Discussionmentioning
confidence: 99%
“…To counter potential problems with resistance, second‐generation transgenic cotton that produces the Bt toxin Cry2Ab in combination with Cry1Ac was developed and introduced into India in 2006. The second‐generation Bt ‐II technology was effective in controlling Cry1Ac‐resistant and Cry2Ab‐susceptible PBW, primarily because Cry2Ab and Cry1Ac bind to different receptors in PBW and also because of the negligible cross‐resistance in PBW to the two toxins . Redundant killing occurs when insects resistant to one Bt toxin are killed by another toxin in a pyramid such as Bt ‐II.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The widespread use of herbicide resistant genotypes eased the workload of conventional farmers, however, it also resulted in increased herbicide residues in feed and human food [38] and within short time their benefits are overcome by resistant weeds. Similar for Bt cotton, after wide spread use, severe yield losses were caused in India in 2016 due to resistant pink bollworm attack [39]. Giving high priority to holistic approaches, the organic sector has a different risk perception and therefore different interpretation of outcomes of risk analyses.…”
Section: The Arguments Of the Organic Sector's Ban On Genetic Engineementioning
confidence: 99%
“…While, a few cases of study in laboratory and field populations showed that the insect could evolve resistance to pyramid crops (Bernardi et al, 2015;Brévault et al, 2013;Fabrick et al, 2015;Wei et al, 2015;Welch et al, 2015). However, study by who reported that the resistance to pyramids is due to similarity of amino acid sequence between Bt toxins, which affect the cross-resistance when the resistance is associated with mutations, that reduce binding to midgut receptor.…”
Section: Resistance To Pyramid Bt Cropsmentioning
confidence: 99%